2012
DOI: 10.1111/j.1651-2227.2012.02754.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing for upper respiratory infections: European primary paediatricians’ knowledge, attitudes and practice

Abstract: There is a clear need for an educational intervention focused on European primary care paediatricians based on the risk-benefit analysis associated with the antibiotic prescribing for minor URIs, to reduce inappropriate prescribing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 24 publications
2
34
0
1
Order By: Relevance
“…Our findings are largely in line with those of previous studies on parental beliefs about antibiotics' benefits for acute respiratory infections, [18][19][20][21][22][23][24][25][26] although our study is among the first to quantify them. Of course, such expectations were not homogeneous across parents and illnesses-parents knew that not using antibiotics is sometimes acceptable, consistent with previous findings.…”
supporting
confidence: 82%
“…Our findings are largely in line with those of previous studies on parental beliefs about antibiotics' benefits for acute respiratory infections, [18][19][20][21][22][23][24][25][26] although our study is among the first to quantify them. Of course, such expectations were not homogeneous across parents and illnesses-parents knew that not using antibiotics is sometimes acceptable, consistent with previous findings.…”
supporting
confidence: 82%
“…Nonetheless, this result compared favourably with overseas studies, 6,19,20 where the reported antibiotic prescription rate for URTI was as high as 42%. 6 Similarly, those studies reported the 2 Respiratory problems among children younger than 5 years per 100 encounters, by general practitioner age and sex, and by season, for the four specified respiratory tract infections, [2007][2008][2009][2010][2011][2012] possibly poor medical knowledge of respiratory infections, 21 physicians' perception of parental satisfaction, 8 and parents' misconceptions and expectations regarding the treatment of RTIs, especially the perceived benefits of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, three of the studies had a response rate less than 50% (29,50,51), which can be a limitation to the generalization of the results of these studies. In some of the studies, participants were from different specialties and treating different infectious diseases (51)(52)(53)(54), while other studies were specific and a certain disease condition such as paediatric common colds (49), URTIs (29,35,50,55,56), and surgical site infections (57). In some of the studies, the authors stated that the respondents may be triggered to the topic and gave socially desirable answers [23].…”
Section: Methodological Qualitymentioning
confidence: 99%
“…The study setting was ambulatory care in eight studies (29,35,48,49,56,(60)(61)(62), hospital setting in seven studies (51,52,54,57,63,64) and both primary and hospital care in four studies (39,50,55,58). Sixteen studies focused solely on physicians, while three studies included pharmacists, patients or the general public.…”
Section:  Characteristics Of Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation